Effects of Anti-TNF Alpha Drugs on Disability in Patients with Rheumatoid Arthritis: Long-Term Real-Life Data from the Lorhen Registry. (6th July 2014) - Filippini, Matteo; Bazzani, Chiara; Atzeni, Fabiola; Sarzi Puttini, Piercarlo; Marchesoni, Antonio; Favalli, Ennio Giulio; Caporali, Roberto; Cavagna, Lorenzo; Gorla, Roberto
Abstract : This study involving 1033 patients with RA confirms the effectiveness of etanercept, adalimumab, and infliximab in reducing RA-related disability even in patients with a history of highly active and longstanding RA. Moreover, we found that the improvement in disability was biphasic, with a marked improvement during the first year of anti-TNF therapy, followed by slower but significant recovery over the subsequent four years.